Salvianolic Acid B Protects Against Fatty Acid-Induced Renal Tubular Injury via Inhibition of Endoplasmic Reticulum Stress - Mai, Xiaoyi; Yin, Xin; Chen, Peipei; Zhang, Minzhou (Frontiers in Pharmacology, 2020)
BBackground/Aims: Obesity-related kidney disease is associated with elevated levels of saturated free fatty acids (SFA). SFA lipotoxicity in tubular cells contributes to significant cellular apoptosis and injury. Salvianolic acid B (SalB) is the most abundant bioactive molecule from Radix Salviae Miltiorrhizae. In this study, we investigated the effect of SalB on SFA-induced renal tubular injury and endoplasmic reticulum (ER) stress, in vivo and in vitro. Methods: C57BL/6 mice were assigned to five groups: a control group with normal diet (Nor), high-fat diet group (HFD), and HFD with 3 different SalB treatment doses, low (SalBL; 3mg/kg), medium (SalBM; 6.25mg/kg), and high (SalBH; 12.5mg/kg) doses. SalB was intraperitoneally injected daily for 4 weeks after 8 weeks of HFD. After 12 weeks, mice were sacrificed and kidneys and sera were collected. Apoptosis and ER stress were induced in human proximal tubule epitelial (HK2) cells by palmitic acid (PA, 0.6mM), tunicamycin (TM, 1μg/ml), or thapsigargin (TG, 200nM) in vitro. Results: C57BL/6 mice fed a high-fat diet (HFD) for 12 weeks exhibited increased apoptosis (Bax and cleaved caspase-3) and ER stress (BIP, P-eIF2α, ATF4, CHOP, ATF6, IRE1α, and XBP1s) markers expression in the kidney, compared with control mice, which were remarkably suppressed by SalB treatment. In vitro studies showed that PA (0.6mM) induced apoptosis and ER stress in cultured HK2 cells. SalB treatment attenuated all the adverse effects of PA. However, SalB failed to inhibit TM (1μg/ml) or TG-induced ER stress in HK2 cells. Conclusion: The study indicated that SalB may play an important role in obesity-related kidney injury via mediating SFA-induced ER stress.